Decomposition of airflow over topography and its application to a topographic blizzard event in central Asia - Ma, Shuping; Cai, Ren; Ran, Lingkun; Jiao, Baofeng; Zhou, Kuo; Guo, Anboyu (Frontiers in Earth Science, 2023)
To better understand the triggering mechanisms of extreme precipitation events in Central Asia due to the complex terrain, a case study of a topographic blizzard that occurred in Xinjiang Province on 30 November 2018 is conducted. The near-surface wind field is decomposed into flow-around and flow-over components to analyze the dynamic and thermodynamic effects of the flow around and over the topography in the Ili River valley and the northern slope of the Tianshan Mountains. The results reveal that the flow around the topography is the dominant component of the flow field that transports water vapor and causes moisture convergence. The symmetric instability observed at the lower level of the snowfall area is attributed to the flow-around wind field, which leads to advective transport of generalized potential temperature and causes changes in potential vorticity, ultimately resulting in symmetric instability. The local variation of stratified instability in the snowfall area is caused by flow-over potential divergence, specifically, the advection of the flow-over wind vertical shear to equivalent potential temperature causes the change of flow-over potential divergence, thus promotes stratified instability. Moreover, the flow-over potential divergence is negatively correlated with the amount of topographic snowfall to a certain extent, which can provide reference for topographic snowfall forecast in the future. Additionally, the cyclonic vorticity in the snowfall area is mainly caused by the flow around topography and flow-around wind produces favorable vortical circulation conditions for snowfall, while the vertical movement near the ground at the snowfall triggering stage is mainly caused by the flow-over component. Furthermore, the flow-over kinetic energy in the snow area is stronger and the work done by the pressure gradient force caused by flow over terrain drives kinetic energy changes.